The need for an antibiotic stewardship program in a hospital using a computerized pre-authorization system - ERTÜRK ŞENGEL, BUKET; BİLGİN, HÜSEYİN; KORTEN, VOLKAN (ELSEVIER SCI LTD, 2019)
Objectives: Antimicrobial stewardship programs (ASPs) have an important role in the appropriate utilization of antibiotics. Some of the core strategies recommended for ASPs are pre-authorization and prospective audit and feedback. In Turkey, a unique nationwide antibiotic restriction program (NARP) has been in place since 2003. The aim of this study was to measure the effect of a prospective audit and feedback strategy system along with the NARP. Methods: A prospective quasi-experimental study was designed and implemented between March and June 2017. A computerized pre-authorization system was used as an ASP strategy to approve the antibiotics. During the baseline period, patients with intravenous (IV) antibiotic use >= 72 h were monitored without intervention. In the second period, feedback and treatment recommendations were given to attending physicians in the case of IV antibiotic use >= 72 h. The modified criteria of Kunin et al. and Gyssens et al. were followed for appropriateness of prescribing. Days of therapy (DOT) and length of stay (LOS) were calculated and compared between the two study periods. Results: A total of 866 antibiotic episodes among 519 patients were observed. A significant reduction in systemic antibiotic consumption was observed in the intervention period (575 vs. 349 DOT per 1000 patient-days; p < 0.001). On multivariate analysis, prospective audit and feedback (odds ratio 1.5, 95% confidence interval 1.09-2.04; p = 0.011) and pre-authorization of restricted antibiotics (odds ratio 1.7; 95% confidence interval 1.2-2.31; p = 0.002) were the predictors of appropriate antimicrobial use. Mean LOS was decreased by 2.9 days (p = 0.095). Conclusions: This study showed that the antimicrobial restriction program alone was effective, but the system should be supported by a tailored ASP, such as prospective audit and feedback. (C) 2019 The Author(s). Published by Elsevier Ltd on behalf of International Society for Infectious Diseases.
Keywords: Antimicrobial stewardship; Days of therapy; Length of stay; ANTIMICROBIAL STEWARDSHIP; CARE; RESISTANCE; IMPACT; POLICY; USAGE; COST